AB0479 Patient outcomes following 10 years of treatment with adalimumab in the DE020 roll-over trial. (23rd January 2014) - Weinblatt, M.E.; Furst, D.E.; Kavanaugh, A.; Faccin, F.; Kupper, H.; Obermeyer, K.; Birbara, C.
Abstract : Background: DE020 was a long-term, open-label (OL) roll-over study for 4 studies in the early development program of adalimumab (ADA). All 4 studies enrolled patients (pts) with active rheumatoid arthritis (RA) and an inadequate response to methotrexate (MTX) and/or other DMARD(s). Objectives: To describe long-term efficacy and safety following up to 10 years (yrs) of ADA exposure in pts with long-standing RA and previous MTX failure. Methods: Adult pts with active RA who completed 1 of 4 ADA early assessment studies were eligible for enrollment in this 10-yr OL roll-over study; pts could receive supplemental DMARD therapy at the investigator's discretion. This post hoc analysis included observed data through 10 yrs of treatment. Baseline demographics and disease characteristics reflected start of the early assessment study. Clinical and functional responses were assessed as the percentage of pts achieving ACR20/50/70 responses, DAS28(CRP) low-disease activity (LDA, ≤3.2) and remission (<2.6) criteria, and normal function (HAQ-DI <0.5) at Yr 10. Safety was assessed in terms of adverse events (AEs) per 100 pt yrs (AE/100PY) for all pts exposed to ADA. Results: A total of 846 pts enrolled in this OL roll-over study. At baseline of the early assessment studies, pts on average were typical of a population with long-standing and active RA: 78% were female, mean age was 55 yrs, mean disease duration was 11.1 yrs, 73% were rheumatoid factor positive, 77% received concomitant MTX, mean DAS28(CRP) was 5.7, mean HAQ-DI was 1.4, and mean CRP was 18.0 mg/L. A total of 286 (33.8%) pts completed 10 yrs of ADA treatment; AEs were the primary reason for study discontinuation (22.9%). The improvements in clinical signs and symptoms initially observed with ADA in the early assessment studies continued through an additional 10 yrs of ADA exposure (Table), with more than one-third (37%) simultaneously achieving LDA and normal function at Yr 10. No new safety signals arose following 5223.9 pt-yrs of ADA exposure, and rates of AEs were consistent with the known safety profile of TNF inhibitors: serious AEs (18.2AE/100PY), serious infections (3.1AE/100PY), TB (0.1AE/100PY), malignancies other than lymphoma and NMSC (1.3AE/100PY), and lymphoma (0.2AE/100PY). Furthermore, there was no increase in the overall mortality rate [SMR (95% CI) =0.69 (0.47, 0.98)]. Conclusions: Treatment with ADA provided disease relief and improved quality of life through 10 yrs in pts with established, severe RA despite DMARD therapy. Disclosure of Interest: M. Weinblatt Grant/Research support from: Abbott, Consultant for: Abbott, D. Furst Grant/Research support from: Amgen, Janssen, Roche, UCB, Consultant for: Amgen, Janssen, Roche, UCB, A. Kavanaugh Consultant for: Abbott, F. Faccin Shareholder of: Abbott, Employee of: Abbott, H. Kupper Shareholder of: Abbott, Employee of: Abbott, K. Obermeyer Shareholder of: Abbott, Employee of: Abbott, C. Birbara: None Declared